Design principles of ships and marine structures - Misra, S. C. 1948- (CRC Press, 2016)
This book discusses naval architecture and marine engineering applications and principles relevant to the design of various systems, examines advanced numerical techniques that can be applied to maritime design procedure at the concept design stage, and offers a comprehensive approach to the subject of ship design. The book begins with an introduction to marine design and the marine environment, describing many of the marine products that are used for transportation, defense and the exploitation of marine resources. It also discusses stability issues relevant to ship design, as well as hydrodynamic aspects of resistance, propulsion, sea keeping and maneuvering, and their effects on design. In addition to covering the various systems and sub-systems that go into making a complex product to be used in maritime environment, the author explains engineering economics and its application in ship design, and provides examples wherever necessary. Contents covered - marine environment, design process, engineering economics, vehicle parameter estimation, stability of floating bodies, hydrodynamic design, hull form design, machinery system, structural design, layout design, design for safety, design for sustainability, design for production, decision-making process and design management.